2016
DOI: 10.1148/rg.2016150133
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of Fat-containing Soft-Tissue Masses at MR Imaging: The Common, the Uncommon, the Characteristic, and the Sometimes Confusing

Abstract: Fat-containing tumors are the most common soft-tissue tumors encountered clinically. The vast majority of fat-containing soft-tissue masses are benign. Lipomas are the most common benign fat-containing masses and demonstrate a characteristic appearance at magnetic resonance (MR) imaging. Less common benign soft-tissue masses include lipoblastoma, angiolipoma, spindle cell lipoma/pleomorphic lipoma, myolipoma, chondroid lipoma, lipomatosis of nerve, lipomatosis, hibernoma, and fat necrosis. Well-differentiated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
71
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(77 citation statements)
references
References 68 publications
1
71
2
Order By: Relevance
“…Liposarcomas represent approximately 20% of all soft tissue sarcomas and are divided into various subtypes including atypical lipomatous tumors/well-differentiated liposarcomas (ALT/WDLs), de-differentiated liposarcoma, myxoid liposarcoma, round cell liposarcomas, and pleomorphic liposarcomas. ALT/WDLs are often difficult to distinguish from benign lipomas on MRI [ 1 , 2 , 6 , 9 , 10 ] and have different treatments as well as prognosis. On MRI, ALT/WDLs are known for having thick septa, lack of capsule with less well-defined margins, nodularity, internal cystic changes, heterogeneity, and enhancement on T2-weighted imaging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liposarcomas represent approximately 20% of all soft tissue sarcomas and are divided into various subtypes including atypical lipomatous tumors/well-differentiated liposarcomas (ALT/WDLs), de-differentiated liposarcoma, myxoid liposarcoma, round cell liposarcomas, and pleomorphic liposarcomas. ALT/WDLs are often difficult to distinguish from benign lipomas on MRI [ 1 , 2 , 6 , 9 , 10 ] and have different treatments as well as prognosis. On MRI, ALT/WDLs are known for having thick septa, lack of capsule with less well-defined margins, nodularity, internal cystic changes, heterogeneity, and enhancement on T2-weighted imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous imaging features on MRI have been reported to facilitate differentiation between these two entities. Location deep to fascia, septations >2 mm thick, heterogeneity, foci of high T2 signal, diameter >5 cm, stranding, nodularity, and cystic changes within the tumor have been reported as being more common in ALT/WDLs than in lipomas [ 1 , 2 , 6 , 7 ]. A representative MR image of an ALT/WDL demonstrating common concerning features is shown in Figure 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Several differences between lipoma and WDLPS on MRI have been described in the literature: size, location, tumour depth and intratumour heterogeneity. However, as there can be considerable overlap between these features, distinguishing between the two tumour types remains difficult, even for trained radiologists. As the differences between lipoma/WDLPS and DDLPS are more obvious, this distinction can accurately be made solely by eye.…”
Section: Introductionmentioning
confidence: 99%
“…The exact reason is unidentified, but the most reasonable hypothesis suggests a nonspecific synovial response to traumatic or inflammatory stimuli more willingly than a neoplasm. Lipoma arborescens can be confidently diagnosed because of its characteristic imaging findings [1,2,[18][19][20][21][22][23][24]. MRI was able to diagnose all the cases of lipoma arborescens in the current series, all complained of painless swelling of the knee and they appear in MRI as intra-articular frond like fat-containing masses at the supra-patellar region (high signal at T1, T2, and suppressed at STIR) and was proved by arthroscopy in agreement with Pushpender Gupta et al [18] who reported similar clinical presentation, and reported its more common predilection to the supra-patellar recess of the knee.…”
Section: Discussionmentioning
confidence: 99%